Framing Environmental Issues in NUOnline and Tajdid.id Online Media - Lilis Muchlisoh; Marya Ulfa; Luluk Fikri Zuhriyah (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2025)
Mass media has a strategic role in shaping the public’s perspective on crucial issues, including environmental issues that are increasingly prominent in global and national discourse. This study aims to analyze how online Islamic media NUOnline and Tajdid.id frame environmental issues through the perspective of Robert N. Entman’s framing theory, which includes four main elements: define problems, diagnose causes, make moral judgments, and suggest remedies. The results of the study show that NUOnline tends to define environmental problems as a form of moral and spiritual crisis, with causes linked to weak religious awareness and the practice of exploiting nature. Moral judgment is conveyed through Islamic teachings on the mandate and responsibility of the caliph on earth, as well as solutions directed at strengthening local religious and cultural values. Meanwhile, Tajdid.id frames environmental issues as structural and multidimensional problems, with an emphasis on collective responsibility between religious communities and the importance of public policy. This media emphasizes a rational and collaborative approach in offering solutions. These findings indicate that although both contain religious values as a moral basis in environmental reporting, differences in ideological orientation and communication approaches result in different framing constructions. This study fills the gap in the study of media framing based on religious values and offers a new perspective on Islamic environmental communication in Indonesia.